2009
DOI: 10.1016/j.devcel.2009.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-α9 Is Required for Fibronectin Matrix Assembly during Lymphatic Valve Morphogenesis

Abstract: SummaryDysfunction of lymphatic valves underlies human lymphedema, yet the process of valve morphogenesis is poorly understood. Here, we show that during embryogenesis lymphatic valve leaflet formation is initiated by upregulation of integrin-α9 expression and deposition of its ligand, fibronectin-EIIIA (FN-EIIIA), in the extracellular matrix. Endothelial cell specific deletion of Itga9 (encoding integrin-α9) in mouse embryos results in the development of rudimentary valve leaflets, characterized by disorganiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
362
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(392 citation statements)
references
References 49 publications
(91 reference statements)
19
362
2
4
Order By: Relevance
“…1C). It was shown that the interaction of FN-EDA with its receptor α9β1 plays a role in the development of lymphatic valves, although both FN-EDA and TN-C were colocalized in developing lymphatic valves (15). We found that blockade of α9 did not cause defects of lymphatic flow (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…1C). It was shown that the interaction of FN-EDA with its receptor α9β1 plays a role in the development of lymphatic valves, although both FN-EDA and TN-C were colocalized in developing lymphatic valves (15). We found that blockade of α9 did not cause defects of lymphatic flow (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Factors, including vascular endothelial growth factor receptor 3 (VEGFR3), lymphatic vessel endothelial hyaluronan receptor 1 (LYVE-1), transcription factor prox-1, and integrins, regulate lymphatic vessel growth and development (9)(10)(11)(12)(13). Among the integrins, α9 integrin (α9 hereafter) is critical for the development of lymphatic valves (14,15). Furthermore, prox-1-induced lymphatic endothelial differentiation is mediated at least in part through α9 (10).…”
mentioning
confidence: 99%
“…These capillaries drain into precollecting and collecting vessels that have continuous, "zipper-like" interendothelial junctions [30] and are surrounded by smooth muscle. Collecting vessels are organized into contractile segments called lymphangions, separated by bileaflet valves, that create the driving force for unidirectional lymph propulsion [30,31,[34][35][36]. Collecting lymphatic vessels that carry lymph to and from the lymph nodes are referred to as afferent and efferent lymphatic vessels, respectively.…”
Section: Lymphatic Physiology and Neogenesismentioning
confidence: 99%
“…Recent studies using genetic mouse models have revealed that several genes play important roles in lymphatic valve development. Defects with lymphatic valve formation have been shown in mice upon suppression of calcineurin/NFATc1 signaling (Norrmen et al 2009), or with genetic deletion / mutation of the following genes, including Foxc2 (Petrova et al 2004), Ephrinb2 (Makinen et al 2005), Itga9 and Fn-EIIIA (Bazigou et al 2009), Pik3r1 (Mouta-Bellum et al 2009) and Akt1 . Mice deficient in Cx37 (connexin-37), a downstream target of FOXC2, were recently shown to display abnormal valve formation (Kanady et al 2011;Sabine et al 2012).…”
Section: Lymphatic Valve Developmentmentioning
confidence: 99%
“…Lymphatic valves are semilunar structures and the valve leaflet is composed of an extracellular matrix core covered by LECs on both sides (Bazigou et al 2009). Recent studies using genetic mouse models have revealed that several genes play important roles in lymphatic valve development.…”
Section: Lymphatic Valve Developmentmentioning
confidence: 99%